2011
DOI: 10.1074/jbc.m110.209924
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Latching of a Regulatory Gate Affords Allosteric Control of Aromatic Amino Acid Biosynthesis

Abstract: The first step of the shikimate pathway for aromatic amino acid biosynthesis is catalyzed by 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase (DAH7PS). Thermotoga maritima DAH7PS (TmaDAH7PS) is tetrameric, with monomer units comprised of a core catalytic (␤/␣) 8 barrel and an N-terminal domain. This enzyme is inhibited strongly by tyrosine and to a lesser extent by the presence of phenylalanine. A truncated mutant of TmaDAH7PS lacking the N-terminal domain was catalytically more active and completely insen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(108 citation statements)
references
References 47 publications
3
105
0
Order By: Relevance
“…S2A) that includes such an ACT domain dimer, similar to that of the regulatory domain of tyrosine hydroxylase (28). However, other architectures are possible, such as that of the tyrosine-binding ACT domain dimer of 3-deoxyheptulosonic acid 7-phosphate synthase (30). Also, as noted above, several possible geometries are possible for the C-terminal four-helix bundle in the activated tetramer.…”
Section: Discussionmentioning
confidence: 99%
“…S2A) that includes such an ACT domain dimer, similar to that of the regulatory domain of tyrosine hydroxylase (28). However, other architectures are possible, such as that of the tyrosine-binding ACT domain dimer of 3-deoxyheptulosonic acid 7-phosphate synthase (30). Also, as noted above, several possible geometries are possible for the C-terminal four-helix bundle in the activated tetramer.…”
Section: Discussionmentioning
confidence: 99%
“…This latter group includes the structurally characterized enzymes from Pyrococcus furiosus (25) and Aeropyrum pernix (26). We recently demonstrated that the DAH7PS from Thermotoga maritima, structurally composed of an ACT domain fused to the N terminus of a catalytic (β/α) 8 barrel, undergoes a remarkable conformational change associated with ligand binding (27). The associated domain reorganization controls enzyme functionality by physically gating substrate access to the active site upon binding of Tyr (Fig.…”
mentioning
confidence: 99%
“…The pathway branches at chorismate, and chorismate mutase catalyzes the formation of prephenate from chorismate, which in turn will form Tyr and Phe. mechanism for elaborating feedback inhibition on DAH7PS activity (4,7,17). The combination of DAH7PS and CM domains may represent another case of this phenomenon.…”
Section: Dah7ps and CM Catalytic Activities Of Wild-type Gspdah7ps Camentioning
confidence: 99%
“…Whereas the type I␤ DAH7PS from Thermotoga maritima undergoes significant ACT domain movement associated with the binding of inhibitor Tyr (7), for other enzymes, such as the type II M. tuberculosis DAH7PS (13) and the type I␣ N. meningitidis DAH7PS (14), allosteric inhibition is conferred by more subtle structural changes and alteration in protein dynamics. The variation in allosteric machinery and mechanism for this enzyme is intriguing both from a mechanistic and evolutionary point of view.…”
mentioning
confidence: 99%
See 1 more Smart Citation